Profil Resiliensi Akademik Mahasiswa Pendidikan Biologi FKIP Universitas Riau selama pandemi COVID-19 - Muhammad Farhan Ali (Pedagogi Hayati, 2023)
This study aims to describe the profile of academic resilience of Biology Education University of Riau students during the COVID-19 pandemic. To answer these objectives, this study used a descriptive research design with a quantitative approach and (online) survey method. The sample for this research is all active students who took online lectures during the COVID-19 pandemic as many as 76 students. Data was obtained by distributing a modified Academic Resilience Scale (ARS-30) questionnaire randomly (online) to all active batches taking online lectures during the COVID-19 pandemic in the form of an electronic questionnaire (google form). Data analysis by calculating the average (mean) academic resilience of Biology Education University of Riau students in terms of three dimensions of academic resilience, namely the dimensions of persistence, reflection and seeking adaptive assistance, as well as negative impacts and emotional responses. Based on the findings of the researchers, it can be concluded that the academic resilience of Biology Education University of Riau students during the COVID-19 pandemic is relatively high in terms of the dimensions of persistence, reflection and seeking adaptive help, as well as adverse impacts and emotional responses. Further research should look at the academic resilience profile after the COVID-19 pandemic and compare it with the academic resilience profile of biology education students at other universities.